Fast Tours and Short Videos. TikTok Napoli, Popular Mediatization of the City and Tourist Consumer Cultures - Recano, Luca (Italian Sociological Review, 2026)
The popular appropriation of TikTok in Naples overlaps with the city’s ongoing touristification, generating distinctive mediatization forms. Within this convergence, a new phase of platformization intersects with the repositioning of micro-businesses and informal labor into tourism-driven economies, supporting ‘touristification from below’. Through vernacular creativity, local actors gain representational agency and reputational capital, challenging institutional prerogatives in destination management and tourist marketing while generating new forms of visibility and value entangled with tourist consumption. Users’ practices – including advertainment and local branding techniques – transform urban spaces, cultural identities and everyday life elements into semiotic resources, easily iconized and reproduced as platform content, participating in the co-production of the city’s image as a tourist consumption site. Drawing on digital ethnography of ‘TikTok Napoli’, this article examines how grassroots platform-mediated practices engage in the spatial division of tourist consumption and what contradictions emerge. TikTok Napoli is conceptualized both as a socio-technical infrastructure and a translocal mediascape, that operates ambiguously. While it enables conventionally marginalized actors to develop creative agency and economic opportunities, it simultaneously reinforces tourist clichés, flattening urban imagery into stereotyped spectacles shaped by algorithmic distribution and market imperatives. Rather than democratizing the urban mediascape, such participatory mediatization exacerbates tourist consumerism and the commodification of urban spaces and experiences. The study contributes to debates on platformization, local branding, and spatialized consumption in urban transformations, offering critical insights into platforms’ socio-spatial integrations and the ambivalent role of digital technologies where urban life and culture become raw material for tourist economies.